Analisis Peran Dimensi-Dimensi Service Quality Dalam Mempengaruhi Keputusan Pembelian Rumah Subsidi Di Kabupaten Gowa - Sri Rahmi; Hasmin Tamsah; Gunawan Bata Ilyas (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2022)
This study aims to analyze the role of the ServQual dimensions (tangible, assurance, responsiveness, empathy, and reliability) in measuring the influence of ServQual on purchasing decisions for subsidized housing in the Gowa Regency. With a quantitative approach, valid data were collected through an online questionnaire from 101 respondents who were Low Income Communities (MBR) who bought subsidized houses in Gowa Regency, South Sulawesi. The data were analyzed using structural equation modeling (SEM) techniques using the AMOS 24 application. The results of the analysis show that assurance is a dimension that cannot be used to measure ServQual, while reliability is the dimension that provides the largest measurement in this study. Overall, ServQual as measured by tangible, responsiveness, empathy, and reliability, have a positive and significant effect on the decision to buy subsidized housing in the Gowa Regency. The results of this study indicate that in the marketing of subsidized housing, the developer's ability to assist the mortgage application process is the main indicator of service quality.